Rehabilitation and Research Priorities in Deafblindness for the Next Decade. (July 2016) - Wittich, Walter; Jarry, Jonathan; Groulx, Geneviève; Southall, Kenneth; Gagné, Jean-Pierre
Purpose: Previous studies have guided the development of deafblindness rehabilitation by reporting on the priorities of researchers and of deafblind individuals; however, service and care providers may be able to bring a different and important perspective to shaping the development of this clinical field and its research. The present study aims to give them a voice in this process. Methods: We conducted a qualitative survey in which 68 stakeholders in deaf-blind rehabilitation from 6 countries described their perceived research and rehabilitation priorities for the coming decade. Verbatim transcripts were analyzed using thematic analysis through open coding, creating categories, and abstraction. Results: Three categories of priorities emerged: those common to rehabilitation and research (such as assistive technology, communication services, and interdisciplinarity), those unique to rehabilitation (such as augmented service provision), and those unique to research (such as recruitment databases and measurement tools). Conclusions: When viewing the findings from within the context of the existing research literature, the overlap indicated that research and rehabilitation efforts are moving in a congruent direction for researchers, service providers, and persons with deafblindness. Future efforts should focus on information exchange in order to improve evidence-based rehabilitation practice.